2023
DOI: 10.1029/2023jd038943
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Summertime Ozone Formation Regime in Southeast Michigan Using MOOSE Ground‐Based HCHO/NO2 Measurements and F0AM Box Model

Ying Xiong,
Jiajue Chai,
Huiting Mao
et al.

Abstract: Ambient ozone (O3) concentrations in Southeast Michigan (SEMI) can exceed the U.S. National Ambient Air Quality Standard (NAAQS). Despite past efforts to measure O3 precursors and elucidate reaction mechanisms, changing emission patterns and atmospheric composition in SEMI warrant new measurements and updated mechanisms to understand the causes of observed O3 exceedances. In this study, we examine the chemical drivers of O3 exceedances in SEMI, based on the Phase I MOOSE (Michigan‐Ontario Ozone Source Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Box models can reasonably capture observed O 3 concentrations when a large fraction of O 3 at a given site is produced by in situ chemistry (Edwards et al, 2013(Edwards et al, , 2014McDuffie et al, 2016;Ninneman & Jaffe, 2021;Xiong et al, 2023). O 3 in photochemically aged air masses depleted of NO x and primary VOCs is likely to be underestimated by a box model, as substantial O 3 production occurs upwind of the location of interest (Xue et al, 2013).…”
Section: Modeling Approachmentioning
confidence: 99%
“…Box models can reasonably capture observed O 3 concentrations when a large fraction of O 3 at a given site is produced by in situ chemistry (Edwards et al, 2013(Edwards et al, , 2014McDuffie et al, 2016;Ninneman & Jaffe, 2021;Xiong et al, 2023). O 3 in photochemically aged air masses depleted of NO x and primary VOCs is likely to be underestimated by a box model, as substantial O 3 production occurs upwind of the location of interest (Xue et al, 2013).…”
Section: Modeling Approachmentioning
confidence: 99%
“…Based on prior analyses of satellite column and ground-based monitoring data, ozone modeling and trend assessments, and weekday-weekend differences, the Lake Michigan Air Directors Consortium (LADCO) had previously identified SEMI as in a transitional regime evolving away from VOC sensitivity towards NO x sensitivity ( [22] and references therein). Xiong et al [23], however, used the observed ratio of formaldehyde (HCHO) to nitrogen dioxide (NO 2 ) in near-surface ambient air measured by the AML during MOOSE and a zero-dimensional (0-D) photochemical box model, F0AM (the Framework for 0-D Atmospheric Modeling), utilizing an extensive set of contemporaneous speciated VOC, NO x , and O 3 measurements to analyze the sensitivity of local ozone in SEMI to VOC and NO x controls. F0AM model sensitivity simulations by Xiong et al [23] suggest that the HCHO/NO 2 ratio for the transition between the VOC-and NO x -limited O 3 production regimes is 3.0 ± 0.3 in SEMI.…”
Section: Local Ozone Production In Semi Is Likely Most Sensitive To V...mentioning
confidence: 99%
“…Xiong et al [23], however, used the observed ratio of formaldehyde (HCHO) to nitrogen dioxide (NO 2 ) in near-surface ambient air measured by the AML during MOOSE and a zero-dimensional (0-D) photochemical box model, F0AM (the Framework for 0-D Atmospheric Modeling), utilizing an extensive set of contemporaneous speciated VOC, NO x , and O 3 measurements to analyze the sensitivity of local ozone in SEMI to VOC and NO x controls. F0AM model sensitivity simulations by Xiong et al [23] suggest that the HCHO/NO 2 ratio for the transition between the VOC-and NO x -limited O 3 production regimes is 3.0 ± 0.3 in SEMI. The midday (12:00-16:00) averaged HCHO/NO 2 ratio during the MOOSE intensive campaign was 1.6 ± 1.0, implying that local O 3 production in SEMI is limited by VOC emissions.…”
Section: Local Ozone Production In Semi Is Likely Most Sensitive To V...mentioning
confidence: 99%
“…O 3 /(NO y -NO x ) and HCHO/NO y were proposed and tested as a means to assess whether tropospheric ozone production was NO x or VOC-limited (Kleinman et al, 2001;Sillman, 1995;Sillman & He, 2002;Tonnesen & Dennis, 2000). Chemical box models often use the ratio of LRO x (radical loss rates of self-reaction) to LNO x (reaction rate loss of OH with NO 2 ) to estimate OPRs, although the transition point between regimes is still debated (Kleinman et al, 2001;Roberts et al, 2022;Schroeder et al, 2017;Sebol et al, 2024;Xiong et al, 2023).…”
Section: Introductionmentioning
confidence: 99%